Dinamika Partai Amanat Nasional di Bali Tahun 1999-2019 - Kusuma, Hendra; Ardhana, I Ketut; Putra, Ida Bagus Gede (Tantular; Vol 5 No 1 (2023): Tantular, 2023)
This Study raises the issue of the dynamics of The National Mandate Party (PAN) in Bali after reforms from 1999 to 2019. The research method used in this study is the historical method using a behavioral approach. The discussion in the study will focus more on the history of party dynamics, political strategy, and contribution of parties to the social-political life of the Balinese people. Sources of data that will be used in this study include two types of data sources, namely primary sources and secondary sources. The results showed that there were ups and downs in the dynamics of PAN in political contestation in Bali. This condition is caused by a misperception of the Balinese people regarding the party platform which is considered an Islamic party. This misperception has an impact on PAN inconsistency in the general election contestation in Bali. In an effort to improve this perception, massive PAN socializes the party’s platform to the community. PAN Bali is also avtive in actualizing the party platform in every process of forming the management to implementing work program based on Pancasila.